The potential of money laundering in the regent election in Indonesia - M. Arief Amrullah (Jurnal Cakrawala Hukum, 2022)
Advances in information technology and globalization processes make it easier for transnational criminal groups to use the legitimate economy to disguise their operations and facilitate the rapid transfer of proceeds of crime to avoid investigation by law enforcement authorities. One of the prominent activities of organized crime is profiting from the illicit drug trade, corruption, or other results obtained or obtained, either directly or indirectly, through the execution of crimes that occur in the global financial system. This methodology makes the transaction appear as a legal business. Therefore, efforts to eradicate money laundering are a dynamic process, moreover, organized crime perpetrators are constantly looking for new ways to carry out their illegal goals. Money launderers also have the opportunity to submit their financial contributions for local elections (Pilkada). The practice of money laundering in elections is very likely to occur due to conditions that trigger opportunities for organized crime groups to launder money.